A comparative study of leptospirosis and dengue in Thai children. - Daniel H Libraty; Khin S A Myint; Clinton K Murray; Robert V Gibbons; Mammen P Mammen; Timothy P Endy; Wenjun Li; David W Vaughn; Ananda Nisalak; Siripen Kalayanarooj; Duane R Hospenthal; Sharone Green; et al. (Public Library of Science (PLoS), 2007)
Leptospirosis is an emerging zoonosis that is often under-recognized in children and commonly confused with dengue in tropical settings. An enhanced ability to distinguish leptospirosis from dengue in children would guide clinicians and public health personnel in the appropriate use of limited healthcare resources.We conducted a prospective, hospital-based, study of children with acute febrile illnesses and dengue in Thailand. Among the children without dengue, we identified those with leptospirosis using anti-leptospira IgM and microscopic agglutination titers in paired acute and convalescent blood samples. We then performed a case-control comparison of symptoms, signs, and clinical laboratory values between children with leptospirosis and dengue. In a semi-rural region of Thailand, leptospirosis accounted for 19% of the non-dengue acute febrile illnesses among children presenting during the rainy season. None of the children with leptospirosis were correctly diagnosed at the time of hospital discharge, and one third (33%) were erroneously diagnosed as dengue or scrub typhus. A predictive model to distinguish pediatric leptospirosis from dengue was generated using three variables: the absolute neutrophil count, plasma albumin, and aspartate aminotransferase levels in the first 72 hours of illness.Unrecognized leptospirosis can be a significant cause of "dengue-like" febrile illness in children. Increased awareness of pediatric leptospirosis, and an enhanced ability to discriminate between leptospirosis and dengue early in illness, will help guide the appropriate use of healthcare resources in often resource-limited settings.